Single-Visit Retreatment in Endodontics: A Comprehensive Review - Mahale, Vivek Devidas; T MDS, Vigneshwar (Journal of Neonatal Surgery, 2025)
Endodontic retreatment aims to address the failure of primary root canal therapy and restore periapical health by eliminating persistent or recurrent infection. Traditionally, retreatment has been performed in multiple visits with the use of intracanal medicaments. However, single-visit retreatment is gaining increasing acceptance with advancements in endodontic technology, rotary instruments, irrigant activation systems, and magnification aids. This review explores the rationale, clinical protocols, advantages, limitations, and evidence base surrounding single-visit retreatment. Current literature indicates that single-visit retreatment can achieve comparable success rates to multiple-visit procedures when performed under strict aseptic conditions and with proper case selection. Emphasis is placed on patient-centered outcomes, microbial considerations, procedural efficiency, and long-term prognosis.